The relationship analysis of the traditional medicine knowledge level and self-medication knowledge level on the practice the use of traditional medicine at the University of Darussalam Gontor - Islamanda, Cania Sofyan; Gani, Andayana Puspitasari; Endarti, Dwi (University Of Darussalam Gontor, 2024)
The use of traditional medicine aims to provide preventive, promotive, curative, and rehabilitative measures against a disease. Self-medication is one of the curative health efforts that is often carried out by the community to prevent the disease they are suffering from, as an act of selecting and using medication without a doctor's prescription to treat disorders and symptoms of disease. This research aims to increase understanding, knowledge, and practice of traditional medicine self-medication. This type of research is observational-quantitative, using a cross-sectional approach, which is a research design to study correlation techniques between risk factors and the factors that influence them. Data collection used questionnaires distributed directly with a sample size of 481 respondents. Descriptive analysis was used to describe the entire research sample data in the form of sociodemographic data, level of knowledge, self-medication, and practice of using traditional medicine. The inferential analysis used is the Spearman rank correlation test to see the relationship between variables. The results of the research show that there is a significant relationship between the level of knowledge of traditional medicine and the practice of using traditional medicine by respondents of (p value=0.001) and r value = 0.146 and there is a significant relationship between knowledge of self-medication and the practice of using traditional medicine of (p value= 0.005) and r value = 0.128 so this research is in the same direction. Keywords: knowledge, practice, self-medication, traditional medicine